Marjinalisasi Seni Prasi: Genealogi Seni Lukis Wayang Bali di Daun Lontar - I Ketut Supir; I Made Pageh (Universitas Hamzanwadi, 2025)
The marginalization of prasi art as a fine art and craft art on palm leaves which is one of Bali's world cultural heritages is fading and losing its taksu, is very interesting to study. Prasi generally contains a narrative puppet theme that contains a moral message in Hinduism teachings. Traces of prasi art have developed since the ancient Balinese era and as a genealogy of Balinese puppet painting. In accordance with the development of the era in this universal era, its existence is marginalized, it is important to understand several causal factors. The study is packaged in the concept of power relation theory (Foucaultian) and postmodern aesthetic theory, as an eclectic analysis tool to answer the problem that there is a power relation at play behind the marginalization of prasi art. The results obtained are that behind the marginalization of prasi art: there is a power relation and ideology of modern art that plays behind the fading taksu prasi and the ideology of pemrasi. Fabrication of prasi artwork (capitalist ideology) to follow consumers in the pemrasi, as a result the theme of the moral message of the puppet in the form of a puppet narrative is changed into a single figure actor in everyday life, so that there is a stripping of the character and charm of the prasi art. Added to the condition of the transfer of generations of prasi art does not occur, ideologically, the formal education policy of the Balinese government does not accommodate it in the local curriculum at all levels of education, as a result of the appreciation of the community and government, the art of prasi is not known to the community and the younger generation has no interest in studying the art of prasi. In fact, foreign visitors are very impressed with the art of prasi which is very unique and the subtle way of working on palm leaves. Some pemrasi in tourism centers (Tenganan Pegringsingan) for example, to meet consumer tastes, there is commodification and fabrication by the prasi craftsman so that the art of prasi loses its identity. As a result of changing the theme of the puppet (narrative) into a single figure by presenting objects of everyday life, becoming calendar souvenirs, and interpreting the needs of tourists themselves, even though schooler tourists are looking for authentic prasi. The ideology of moneytheism, the government and society's neglect of the art of prasi has resulted in the world heritage of prasi art losing its charm, prestige, and the function and meaning of its authenticity, as a character builder of the Balinese people.